2009
DOI: 10.1002/pca.1172
|View full text |Cite
|
Sign up to set email alerts
|

Optimised separation procedures for the simultaneous assay of three plant hormones in liquid biofertilisers

Abstract: A simple and rapid sample preparation procedure followed by RP-HPLC with UV detection was optimised and developed for simultaneous quantification and identification of three plant hormones namely, IAA, GA(3) and ABA in the liquid biofertilisers. This procedure allows quantification of the three plant hormones in their natural states without any prior derivatisation step. The results presented illustrate that the contents of the three plant hormones depended on the type of fruit wastes, fermentation time and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In previous studies, several sample pretreatment methods have been developed. These methods generally involved liquid extraction with different acid or alkaline solvents and further purifications via solid phase extraction (SPE) with a wide variety of sorbents, i.e., reversed-phase, immunoaffinity or polymeric materials [6][7][8][9]. However, most of SPE cartridges mainly targeted several compounds with similar chemical properties for multiresidue analysis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, several sample pretreatment methods have been developed. These methods generally involved liquid extraction with different acid or alkaline solvents and further purifications via solid phase extraction (SPE) with a wide variety of sorbents, i.e., reversed-phase, immunoaffinity or polymeric materials [6][7][8][9]. However, most of SPE cartridges mainly targeted several compounds with similar chemical properties for multiresidue analysis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have described the MSbased analysis of endogenous phytohormones [7][8][9][10]. However, the MS-based methods still have been restricted to achieve satisfactory ionization efficiency for negatively charged acidic phytohormones, which is mainly due to the low MS response of acidic analytes [11,12], serious matrix effect [13,14], and interference among analytes [15].…”
Section: Introductionmentioning
confidence: 99%
“…exchange ability, is well exploited for a rapid and effective purification process, 25,27,[32][33][34] and it is in good conformity with the analysis of multiple phytohormones which present diverse structural characteristics. Besides, it is reported that the mixedmode cartridges are able to significantly decrease the ion suppression effects of the plant matrix in MS detection.…”
Section: Huwei Liumentioning
confidence: 99%
“…Therefore, LC coupled with various types of detectors is the most commonly applied method for hormone determination. 29,34,[46][47][48] Two-dimensional (2D) LC has been employed in the quantification of plant hormones. Dobrev et al 33 developed a 2D-LC method in 'heart cutting' mode, which efficiently removed the coeluting contaminants with indole-3-acetic acid (IAA) and ABA.…”
Section: Analytical Approachesmentioning
confidence: 99%